On what we know about chance - Arntzenius, F; Hall, N (2003)
The 'Principal Principle' states, roughly, that one's subjective probability for a proposition should conform to one's beliefs about that proposition's objective chance of coming true. David Lewis has argued (i) that this principle provides the defining role for chance; (ii) that it conflicts with his reductionist thesis of Humean supervenience, and so must be replaced by an amended version that avoids the conflict; hence (iii) that nothing perfectly deserves the name 'chance', although something can come close enough by playing the role picked out by the amended principle. We show that in fact there must be 'chances' that perfectly play what Lewis takes to be the defining role. But this is not the happy conclusion it might seem, since these 'chances' behave too strangely to deserve the name. The lesson is simple: much more than the Principal Principle - more to the point, much more than the connection between chance and credence - informs our understanding of objective chance.